Case report: A case of corneal epithelial injury associated with Pthiriasis palpebrarum - Wang, Da-Hu; Liu, Xin-Quan (Frontiers in Medicine, 2022)
Significance: Phthiriasis palpebrarum is an uncommon infection due to Phthirus pubis inoculating the eyelashes and surrounding tissues of the eye. Because of its rarity, it may be misdiagnosed as blepharitis or conjunctivitis clinically. Purpose: This report described a rare case of corneal epithelial injury associated with Phthiriasis palpebrarum. Case Report: A 59-year-old woman presented with one month history of repeated episodes of itching and irritation symptoms in both eyes. A slit-lamp examination was performed, which revealed mild conjunctival hyperemia and corneal epithelial defects in both eyes. On closer examination, crab-like lice, nits, and red pinpoint excretions were seen on her eyelashes and eyelids bilaterally. Corneal fluorescein staining in both eyes was observed, and tear film break-up time (BUT) in each eye was 2 seconds. Numerous lice were also found attached to the scalp hair. Therefore, a clinical diagnosis of corneal epithelial injury associated with Pthiriasis palpebrarum was made. For treatment, eyelashes with nits and/or lice were removed mechanically with a fine tweezers. Then, 0.01% Hypochlorous Acid eye wash was used to clean the eyelid margin twice daily. Also, she was prescribed a combination of Vitamin A Palmitate eye gel 3 times a day and Tobradex® eye ointment once daily. Meanwhile, the patient was provided with suggestions on how to improve personal hygiene and environmental hygiene, including cutting of the scalp hair and the application of 0.01% permethrin rinse. One week later, no evidence of lice and nits of the eyelashes and scalp hair was found, and the patient's symptoms and signs also improved significantly. Conclusion: This rare case suggested that the eyelashes of patients presenting with itching and irritation symptoms should be carefully examined with a slit-lamp. Besides removal of the parasites, attention should be paid to the treatment of corneal epithelial injury associated with Pthiriasis palpebrarum.